2016
DOI: 10.1038/npp.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of D1/5 Dopamine Receptors: A Common Mechanism for Enhancing Extinction of Fear and Reward-Seeking Behaviors

Abstract: Dopamine is critical for many processes that drive learning and memory, including motivation, prediction error, incentive salience, memory consolidation, and response output. Theories of dopamine's function in these processes have, for the most part, been developed from behavioral approaches that examine learning mechanisms in appetitive tasks. A parallel and growing literature indicates that dopamine signaling is involved in consolidation of memories into stable representations in aversive tasks such as fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…Salience signalling and salience driven-learning have been strongly associated with dopaminergic signalling (Abraham et al, 2016) and both the amygdala and the orbitofrontal cortex receive extensive mesocortical and mesolimbic dopaminergic inputs (Meador-Woodruff et al, 1997).…”
Section: Valence-specific Effects Of Ketaminementioning
confidence: 99%
“…Salience signalling and salience driven-learning have been strongly associated with dopaminergic signalling (Abraham et al, 2016) and both the amygdala and the orbitofrontal cortex receive extensive mesocortical and mesolimbic dopaminergic inputs (Meador-Woodruff et al, 1997).…”
Section: Valence-specific Effects Of Ketaminementioning
confidence: 99%
“…An advantage of a genetic approach to the D1 receptor is that knockouts are specific to that receptor, whereas pharmacological approaches are not specific, targeting D1 and D5 receptors. We have previously reported that pharmacological activation of the D1/5 receptor enhances fear extinction in male C57BL/6 mice (Abraham et al, 2016). To test whether this effect required D1 receptors, we examined the effects of the D1/5 agonist SKF81297 in the D1 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the previously observed enhancements of fear extinction induced by a D1/D5 agonist (Abraham et al, 2016) could be attributed to pharmacological activation of D5 receptors, we tested the effect of SKF 81297 on fear extinction in D1 KO. On Day 1, naïve subjects received a 12-min exposure to the context with four unsignaled shocks (2s, 0.35 mA), delivered at 2.5, 5, 9, and 11.5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations